Realism - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General

My Contraband (1863) - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General

James Family - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General

Henry Ward Beecher - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General

John Brown - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Keywords: Literary Criticism / American / General; Literary Criticism / General

Virginia Woolf's Jacob's Room: An Introduction and Annotations. - Neverow, Vara (2007)
Keywords: dept.eng; faculty_collection; sabbatical_report

American Pantheon: Poems. - Mock, Jeff (2005)
Keywords: dept.eng; faculty_collection; sabbatical_report

Poetic Healing of the Collective Black Mind: The Example of Langston Hughes and Maya Angelou. - Ogbaa, Kalu (2003)
Keywords: dept.eng; faculty_collection; sabbatical_report

Seven Holy Women Among the Desert Fathers in the First English Edition of Vitas Patrum. - Holbrook, Sue Ellen (Spring;English., 2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

The Jumper. - Parrish, Tim (2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

[A Book on Blake] - Rosso, G. Anthony (2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

Robert Blake: His Watercolors and His Poetry. - Rosso, Tony (fall : English., 2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

The Gendered Revolution in Writing: The Story of the First Prose Masterpiece in Western Civilization. - Blackmer, Corinne (2000)
Keywords: dept.eng; faculty_collection; sabbatical_report

Fall 2009 Sabbatical Leave Follow-Up Report - McEachern, Robert (2009)
I was awarded sabbatical leave for Fall 2009. My sabbatical proposal was titled “How Web 2.0 Technologies Are Transforming Writing in Nonprofit Organizations.” My plan, as laid out in my sabbatical proposal, involved tracking and analyzing the online presence of 3-5 nonprofit organizations, and reporting on the ways the nature of their organizational writing had changed, directly and indirectly, as a result of the use of web 2.0 technologies, including blogs, wikis, and social networking sites such as Facebook and Twitter.
Keywords: dept.eng; faculty_collection; sabbatical_report

Bear Country - Sonnenschein, Dana (NFSPS, 2009)
Keywords: Bears; Poetry; dept.eng; faculty_collection

Torch Lake & Other Poems - Johnson, Brian (Del Sol Press, 2008)
Keywords: 21st century; 21st century; American poetry; Prose poems, American; American poetry; SCSU Faculty Scholar Award; award_winner; dept.eng; faculty_collection

Grace Cavalieri Interviews Vivian Shipley - Cavalieri, Grace; Shipley, Vivian (2007)
Keywords: 21st century; 21st century; Poets, American; American poetry; Interviews; award_winner; dept.eng; faculty_collection

General Ojukwu: The Legend of Biafra - Ogbaa, Kalu (Triatlantic African history-makers series, 2007)
Keywords: 1960-1975; Africa; Africa; Biography; Biography; Nigeria; Biography; Statesmen; Ojukwu, Chukwuemeka Odumegwu, 1933-2011; Politicians; Politics and government; dept.eng; faculty_collection

Freer - Hochman, Will (Pecan Grove Press, 2006)
Keywords: dept.eng; faculty_collection

Natural Forms: Poems - Sonnenschein, Dana (Word Press, 2006)
Keywords: Nature; Poetry; dept.eng; faculty_collection

Conscience and Purpose: Fiction and Social Consciousness in Howells, Jewett, Chesnutt, and Cather - Petrie, Paul R. (Studies in American literary realism and naturalism, 2005)
"In a series of influential essays that appeared in Harper's, W.D. Howells argued for literature as a vehicle for social change. Literature could and should, Howells suggested, mediate across divisions of class and region, fostering cross-cultural sympathies that would lead to comprehensive social and ethical reform." "Paul R. Petrie explores the legacy of Howells's beliefs as they manifest themselves in his fiction and in the works of three major American writers - Charles W. Chesnutt, Sarah Orne Jewett, and Willa Cather. Each author struggled to adapt Howells's social-ethical agenda for literature to his or her own aesthetic goals and to alternative conceptions of literary purpose. Jewett not only embraced Howell's sense of social mission but also extended it by documenting commonplace cultural realities in a language and vision that was spiritual and transcendent. Chesnutt sought to improve relations between Anglo readers and African Americans, but his work, such as The Conjure Woman, also questions literature's ability to repair those divides." "Finally, Petrie shows how Cather, as she shifted from journalism to fiction writing, freed herself from Howells's influence. Alexander's Bridge (1912) and O Pioneers! (1913) both make reference to social and material realities but only as groundwork for character portrayals that are mythic and heroic. The result of Petrie's exploration is a refreshing reassessment of Howell's legacy and its impact on American literature and social history at the turn of the century."--Jacket.
Keywords: Chesnutt, Charles W. (Charles Waddell), 1858-1932; Ethics; American fiction; Ethics; Cather, Willa, 1873-1947; Ethics; Howells, William Dean, 1837-1920; Ethics; Jewett, Sarah Orne, 1849-1909; History and criticism; Ethics in literature; Literature and society; SCSU Faculty Scholar Award; United States; Social ethics in literature; Conscience in literature; award_winner; dept.eng; faculty_collection

Laws of My Nature: Poems - Schilpp, Margot (Carnegie Mellon poetry, 2005)
Keywords: American poetry; dept.eng; faculty_collection

Hardboot: Poems New & Old - Shipley, Vivian (Louisiana Literature Press, Southeastern Louisiana University, 2005)
Keywords: Poets, American; dept.eng; faculty_collection

Caduceus: Poets at Art Place V.3 - Shipley, Vivian; Fusco, Tony; Yale University School of Medicine Yale Medical Group Art Place; Yale Medical Group (Yale Medical Group Art Place, 2005)
Poetry included in the partial contents note is composed of contributions from the faculty, staff, students and alumni of Southern Connecticut State University.
Keywords: Connecticut; Literature and science; New Haven; Literature and science; Poetry; Poetry; United States; United States; New Haven (Conn.); dept.eng; faculty_collection

No Angels but These - Sonnenschein, Dana (Main Street Rag's editor's choice chapbook series, 2005)
Keywords: dept.eng; faculty_collection

The Nigerian Americans - Ogbaa, Kalu (New Americans (Westport, Conn.), 2003)
Keywords: Nigerian Americans; Immigrants; Social conditions; United States; Nigerian Americans; dept.eng; faculty_collection

Gleanings: Old Poems, New Poems - Shipley, Vivian (Louisiana Literature Press, 2003)
Keywords: award_winner; dept.eng; faculty_collection

Corvus: Poems - Sonnenschein, Dana (Wind, 2003)
Fisher-Wirth, Ann W. Trinket poems.
Keywords: Corvus; Poetry; dept.eng; faculty_collection

Letters to J.D. Salinger - Kubica, Chris; Hochman, Will (University of Wisconsin Press, 2002)
"He published his only novel more than fifty years ago. He has hardly been seen or heard from since 1965. Most writers fitting such a description are long forgotten, but if the novel is The Catcher in the Rye and the writer is J.D. Salinger ... well, he's the stuff of legends, the most famously reclusive writer of the twentieth century. If you could write to him, what would you say?" "Salinger continues to maintain his silence, but Holden Caulfield, Franny and Zooey, and Seymour Glass - the unforgettable characters of his novel and short stories - continue to speak to generations of readers and writers. Letters to J.D. Salinger includes more than eighty personal letters addressed to Salinger from well-known writers, editors, critics, journalists, and other luminaries, as well as from students, teachers, and readers around the world, some of whom have just discovered Salinger for the first time. Their voices testify to the lasting impression Salinger's ideas and emotions have made on so many diverse lives."--Jacket.
Keywords: Correspondence; Authors and readers; Salinger, J. D. (Jerome David), 1919-2010; United States; Authorship; dept.eng; faculty_collection

A Century of Nigerian Literature: A Select Bibliography - Ogbaa, Kalu (Africa World Press, 2002)
Keywords: Bibliography; Nigerian literature; dept.eng; faculty_collection

When There Is No Shore - Shipley, Vivian (Word Press, 2002)
Keywords: Kentucky; Poetry; dept.eng; faculty_collection

Walking Blues: Making Americans from Emerson to Elvis - Parrish, Timothy (University of Massachusetts Press, 2001)
"Shows how our American social, racial, and ethnic conflicts often mark the starting point for the various acts of creation through which we make and remake ourselves as Americans."--Cover.
Keywords: Civilization; Intellectual life; National characteristics, American; Cultural pluralism; Parrish; Philosophy; Blues (Music); Philosophy; United States; Social aspects; United States; United States; Popular culture; United States; Pragmatism; United States; award_winner; dept.eng; faculty_collection

Poetry Does Theology: Chaucer, Grosseteste, and the Pearl-Poet - Rhodes, James Francis (University of Notre Dame Press, 2001)
Keywords: Criticism and interpretation; Langland, William, 1330?-1400? Piers Plowman; Chaucer, Geoffrey, -1400. Canterbury tales; Christian poetry, English (Middle); England; Grosseteste, Robert, 1175?-1253; History; History and criticism; Theology; History and criticism; Theology in literature; English poetry; Middle Ages, 600-1500; Patience (Middle English poem); Purity (Middle English poem); Pearl (Middle English poem); Middle English, 1100-1500; award_winner; dept.eng; faculty_collection

The World's Last Night: Poems - Schilpp, Margot (Carnegie Mellon poetry, 2001)
Keywords: American poetry; Women authors; dept.eng; faculty_collection

Down of Hawk: Poems - Shipley, Vivian (Sow's Ear Press, 2001)
Keywords: dept.eng; faculty_collection

Fishing Poems. - Shipley, Vivian (Pudding House Publications chapbook series, 2001)
Keywords: dept.eng; faculty_collection

Panhandler: Special Issue: Photo/Text. - Shipley, Vivian (English Dept. of the University of West Florida, 2001)
Keywords: 20th century; Literature, Modern; dept.eng; faculty_collection

Self-Portrait - Johnson, Brian (Edition key satch(el) ; v. 1, no. 3, 2000)
Keywords: dept.eng; faculty_collection

Red Stick Men: Stories - Parrish, Tim (University Press of Mississippi, 2000)
The characters in these stories "are always on the verge of disasters that emanate from the hard living they endure in the city they call 'Red Stick,'" i.e., Baton Rouge, Louisiana.--Jacket.
Keywords: Baton Rouge; Fiction; Fiction; Baton Rouge (La.); Louisiana; Oil industry workers; Social life and customs; dept.eng; faculty_collection

Fair Haven - Shipley, Vivian (Negative Capability Press, 2000)
Keywords: dept.eng; faculty_collection

The misunderstood discipline of composition studies [3] - Hood, C.L. (Chronicle of Higher Education, 2003)
Keywords: dept.eng; ⛔ No DOI found

Illusions of a public, locations of conflict: Feeling like populace in William Dean Howells' A Hazard of New Fortunes - Stretch, C. (American Literary Realism, 2003)
Keywords: dept.eng; ⛔ No DOI found

Spectacle at the disco: Boogie nights, soundtrack, and the New American musical - Ritter, K. (Journal of Popular Film and Television, 2001)
In our postmodern visual culture, the idea of spectacle conjures images of excess. In defining spectatorship, we emphasize the visual, drawing physical eyewitnesses toward the spectacular moment itself and into the reification of that moment on the film screen. However, recent Hollywood cinema has challenged the notion that all spectacle must take place within the realm of the visual, as many films strive to reach spectators aurally, via their soundtracks. In particular, popular song has been used in many commercially successful films to re-create each spectator's relationship with his or her past. Films with best-selling pop soundtracks, such as The Wedding Singer and Romy and Michelle's High School Reunion, among others, have financially exploited the spectator's attention to familiar song within comedic narratives, prompting viewers to purchase collections of songs they may already own, motivated by nostalgia and pleasant rearrangements of these songs within light, entertaining narratives. In other cases, “retro” films such as 54 and The Last Days of Disco have attempted to capitalize on the popularity of musical trends, such as disco, to revisit what the “scene” meant to its patrons, as well as what disco might mean commercially to new generations. But rarely do the songs in this type of film serve as anything but collective backdrop or the means by which a filmmaker might establish setting, particularly in terms of a decade. They merely reconfigure radio programming, reorder Top 40 hits for a theatrical space. © 2001 Taylor & Francis Group, LLC.
Keywords: dept.eng

Charles Brockden Brown's Ormond, property exchange, and the literary marketplace in the early American republic - Ellis, S. (Studies in the Novel, 2005)
Keywords: dept.eng; ⛔ No DOI found

The paper bag principle: Of the myth and the motion of colorism - Kerr, A.E. (Journal of American Folklore, 2005)
This article, extracted from a larger study, is attentive to the national folk culture of African-American communities - especially rumor and legend - in a number of city centers. The study begins with Washington, D.C., as a representative model to examine the role of complexion-related lore in black neighborhoods, organizations, and institutions, and then extends outward to other urban areas. Complexion lore, the article argues, functioned as a sophisticated negotiation of racism, wherein black residents complicated American urban principles of inclusion and exclusion by integrating color notions into institutional oral history. Copyright © 2005 by the Board of Trustees of the University of Illinois.
Keywords: dept.eng; dept.wgs

The economics of authorship: Online paper mills, student writers, and first-year composition - Ritter, K. (College Composition and Communication, 2005)
Using sample student analyses of online paper mill Web sites, student survey responses, and existing scholarship on plagiarism, authorship, and intellectual property, this article examines how the consumerist rhetoric of the online paper mills construes academic writing as a commodity for sale, and why such rhetoric appeals to students in first-year composition, whose cultural disconnect from the academic system of authorship increasingly leads them to patronize these sites.
Keywords: dept.eng; ⛔ No DOI found

Reviewers reviewed: John Davis and the early American leterary field - Ellis, S. (Early American Literature, 2007)
Keywords: dept.eng

Opinion: Ethos interrupted: Diffusing "star" pedagogy in creative writing programs - Ritter, K. (College English, 2007)
Keywords: dept.eng; ⛔ No DOI found

Popular millenarianism and empire in Blake's night thoughts - Rosso, G.A. (Blake, Modernity and Popular Culture, 2007)
Keywords: dept.eng

Empathy and identity in Vernon Lee's Hauntings - Fluhr, N. (Victorian Studies, 2006)
Keywords: dept.eng

Postmodernism and the politics of “culture” - Katz, A. (Postmodernism and the Politics of "Culture", 2000)
Postmodernism and the Politics of ‘Culture’ is a comparative critical analysis of the political and intellectual ambitions of postmodernist critical theory and the academic discipline of cultural studies. Katz’s polemical aim is to show that cultural studies comes up short in both areas, because its practitioners focus on too-narrow issues-primarily, celebrating the folkways of micro-communities-while denying the very possibility of studying, understanding, and changing society in any comprehensive way and to any universally beneficial purpose. He argues that scholars and activists alike would do well to make use of the analytical tools of postmodernist critical theory, whose practitioners acknowledge the political significance of the differences between social groups, but do not consider them to be unbridgeable, and so seek to develop a set of practices for creating a truly inclusive, truly democratic public sphere. © 2000 Taylor & Francis. All rights reserved.
Keywords: dept.eng

Reflections: neurology and the humanities. You had the choice, Martha. - Shipley, Vivian (Neurology, 2009)
Keywords: *Abortion, Induced/es [Ethics]; *Abortion, Induced/px [Psychology]; *Caregivers/px [Psychology]; *Lesch-Nyhan Syndrome/ge [Genetics]; *Maternal Behavior/px [Psychology]; *Neurology/es [Ethics]; Abortion, Induced; Adult; Caregivers; Choice Behavior; Choice Behavior/es [Ethics]; Female; Humans; Infant; Lesch Nyhan syndrome; Lesch-Nyhan Syndrome; Lesch-Nyhan Syndrome/pp [Physiopathology]; Male; Maternal Behavior; Muscle Weakness; Muscle Weakness/ge [Genetics]; Neurology; Poetry as Topic; Self-Injurious Behavior; Self-Injurious Behavior/ge [Genetics]; Self-Injurious Behavior/pc [Prevention & Control]; adult; article; automutilation; caregiver; decision making; dept.eng; ethics; female; genetics; human; induced abortion; infant; literature; male; maternal behavior; muscle weakness; neurology; pathophysiology; psychological aspect

The Emotional Effects of Literacy: Vietnamese Women Negotiating the Shift to a Market Economy - Crawford, I.W. (WOMEN and LITERACY, 2007)
Vietnam's 1986 doi moi reforms are transforming Vietnam from a socialist economy to a socialist market economy. In addition to liberalized laws allowing
Keywords: dept.eng

An American perspective on equal educational opportunities - Russo, C; Perkins, B (Perspectives in Education, 2004)
The United States Supreme Court ushered in a new era in American history on May 17, 1954 in its monumental ruling in Brown v Board of Education, Topeka, Kansas. Brown is not only the Court's most significant decision on race and equal educational opportunities, but also ranks among the most important cases it has ever decided. In Brown a unanimous Court struck down the pernicious doctrine of “separate but equal” in holding that the de jure segregation of students in public schools on the basis of race deprived minority children of equal educational opportunities in violation of the Equal Protection Clause of the Fourteenth Amendment. In addition to its impact on school desegregation, Brown has been the catalyst for revolutionary change influencing just about every facet of American society. Given the breadth of changes that it spawned, this article briefly reviews the Supreme Court's ruling in Brown before turning to the two most important educational areas where it has been the key, namely special education and sexual harassment.
Keywords: dept.eng; ⛔ No DOI found

Collegiality and tenure - Hood, CL (Academe-Bulletin of the Aaup, 2002)
Keywords: dept.eng; ⛔ No DOI found

Art and the transitional object in vernon lee's supernatural tales (review) - Fluhr, Nicole (Victorian Studies, 2009)
Keywords: dept.eng

The letter and the law, or how caroline norton (Re)Wrote female subjectivity - Fluhr, Nicole (Tulsa studies in women's literature, 2009)
Keywords: dept.eng; ⛔ No DOI found

Book Review: J. a. burrow, the poetry of praise . (cambridge studies in medieval literature, 69.) cambridge, eng., and new york: cambridge university press, 2008. pp. vii, 196. 90. - Rhodes, Jim (Speculum, 2009)
Keywords: book.review; dept.eng

Book Review: The invention of hugo cabret, brian selznick. scholastic press, new york (2007) - Hochman, Will (Computers and Composition, 2008)
Keywords: book.review; dept.eng

Emotional Expression in Malory's Elaine of Ascolat - Holbrook, Sue Ellen (Parergon, 2007)
Shrieks and complaints, accompanied by body language, contribute markedly to Malory's representation of Elaine of Ascolat's emotionality. Elaine's two shrieks echo Lancelot's and indicate change from sorrow for a wounded beloved to heartbreak when he rejects her. When Elaine is compared with speakers in love lyrics, allegories, and romances, the thoughts in her unarticulated complaints after the pained second shriek may be understood and related to her defence of complaint and perseverance in love despite rejection. Similarly, Elaine's complaint letter, including its overlooked moan to ladies, reflects a state of tranquility and brings about a just resolution.
Keywords: dept.eng

Ethos interrupted: diffusing "Star" pedagogy in creative writing programs - Ritter, Kelly (College English, 2007)
Keywords: dept.eng

Honors college, honors 298: special topics, 3 credits - Charpie, John; Shea, Michael (Honors in Practice, 2006)
Keywords: dept.eng; dept.hon; ⛔ No DOI found

“Their calling me ‘mother’ was not, i think, altogether unmeaning”: Mary Seacole's maternal personae - Fluhr, Nicole (Victorian Literature and Culture, 2006)
Keywords: dept.eng

Incorporating reflection into business communication service-learning courses: - Mceachern, Robert W (Business Communication Quarterly, 2006)
Keywords: dept.eng